The role of SMEs in a global economy: A comparative analysis with large corporates - Al-Najjar, Ahmad (2013)
This paper reveals the importance of the Small and Medium Enterprises (SMEs) in their economies worldwide. It will illustrate the influences caused by some SMEs operating in four major economies including USA, Germany, China and India, and compare their results with large corporates within the same country. The data analysis in this research is unique as it measures the relationship between major indicators of the economy like GDP, unemployment and inflation, along with the performance of both SMEs and large corporates. A broad understanding to various SME definitions around the world is also presented in this paper. It will support the theory that globalization has been one of the key drivers to the success of the SME sector around the world along with applications of new technologies. It is also established that SMEs were more resilient to systematic financial shocks when compared to larger sized companies.